HELP: a catalogue of 170 million objects, selected at 0.36–4.5 μm, from 1270 deg2 of prime extragalactic fields. Issue 1 (10th September 2019) - Shirley, Raphael; Roehlly, Yannick; Hurley, Peter D; Buat, Veronique; Campos Varillas, María del Carmen; Duivenvoorden, Steven; Duncan, Kenneth J; Efstathiou, Andreas; Farrah, Duncan; González Solares, Eduardo; Malek, Katarzyna; Marchetti, Lucia; et al.
ABSTRACT: We present an optical to near-infrared (NIR) selected astronomical catalogue covering 1270 deg 2 . This is the first attempt to systematically combine data from 23 of the premier extragalactic survey fields – the product of a vast investment of telescope time. The fields are those imaged by the Herschel Space Observatory that form the Herschel Extragalactic Legacy Project (HELP). Our catalogue of 170 million objects is constructed by a positional cross-match of 51 public surveys. This high-resolution optical, NIR, and mid-infrared catalogue is designed for photometric redshift estimation, extraction of fluxes in lower resolution far-infrared maps, and spectral energy distribution modelling. It collates, standardizes, and provides value added derived quantities including corrected aperture magnitudes and astrometry correction over the Herschel extragalactic wide fields for the first time. grizy fluxes are available on all fields with g -band data reaching 5σ point-source depths in a 2 arcsec aperture of 23.5, 24.4, and 24.6 (AB) mag at the 25th, 50th, and 75th percentiles, by area covered, across all HELP fields. It has K or K_s coverage over 1146 deg 2 with depth percentiles of 20.2, 20.4, and 21.0 mag, respectively. The IRAC Ch 1 band is available over 273 deg 2 with depth percentiles of 17.7, 21.4, and 22.2 mag, respectively. This paper defines the 'masterlist' objects for the first data release (DR1) of HELP. This large sample of standardized total and corrected aperture fluxes, uniform quality flags, and completeness measures provides large well-understood statistical samples over the full Herschel extragalactic sky.